Micro-Environmental status of a dissected highland (College Tilla) of Agartala city, North East india - Sudip Dey (Indonesian Journal of Geography, 2007)
This paper assesses the present micro-environmental conditions of a dissected highland", College Tilla of Agartala city of North-East India. Geomorphologically Agartala city is located in a part of the basin of R Haora which consists of two main geomorphic units namely dissected high lands or tilla lands and adjacent flat alluvium lands. The elevated geomorphology of the tillalands play important role for the development and preservation of typical high landenvironment and rich ecological resources in some pockets of flat alluvium of R Haora basin for long time. Since the urban activities started on College Tilla only during early 2dh century the variation of flora and fauna of the tilla land is still.remarkable. During the recent period rapid extension of Agartala city causes theproblem of geomorphic degradation and affects the natural environmentalcondition of the area. Due to the construction of the buildings, roads, boundaries, water pipe lines etc the dense vegetation cover is removed rapidly and as a result of that now soil erosion and medium size land slides are becoming very commonfeatures in the city. Besides that the ecology of this area is now under serious degradation due to desperate human interventions on the tilla lands of Agartala City